Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

solve the following system of equations. y = -2x - 9 and 2x + 3y = -9

Sagot :

Concerning the interrogate, the retort to such is identified as the following,,

Convert the Slope-Intercept Form to General Form:
Y = -2x - 9 ==> 2x + y = -9

Evaluate:
2x + y = -9
2x + 3y = -9

Multiply the X factors by each other, making one of the products opposite:

-2(2x + y) = -9 ==> -4x - 2y = 18
2(2x + 3y) = -9 ==> 4x + 6y = -18

Add the expressions:
-4x - 2y = 18
4x + 6y = -18
————————
4y = 0
Y = 0

Now, substitute the zero within one of the equations:
2x + 3y = -9
2x + 3(0) = -9
2x = -9
X = -4.5

Thus, (-4.5,0)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.